Exploring the use of budgets by small businesses in the township of Sharpeville - Thithi, Mpho Jeannette (Vaal University of Technology, 2021)
The South African government recognises the small, micro and medium enterprises (SMMEs) for their potential to reduce unemployment and poverty by creating job opportunities, enhancing skills, contributing to the country’s gross domestic product (GDP) and, ultimately, improving the standard of living. The SMMEs in South Africa have high failure rates despite the government’s efforts to develop the SMME sector. The inability to budget, among other factors, is identified as one of the factors that contribute to the failure rate. The main aim of this research study was to establish whether small business owners (formal and informal) in the retail and service sectors in Sharpeville make use of budgets as part of their business practice. To fulfil the primary aim, the study set out secondary objectives to establish whether small businesses (formal and informal) in the retail and service sectors used budgets and determine the types of budgets used, the purpose for which budgets are used, the perception on the use of budgets and the reasons for non-use of budgets. Data were collected by means of a self-administered questionnaire with closed-ended questions from 100 respondents. The application of descriptive statistics was conducted through IBM SPSS version 27 to analyse data collected. The results of this study revealed that small business owners (formal and informal) in the retail and service sectors in Sharpeville do not make use of budgets as part of their business practice. The main reason for small business owners to not make use of budgets was because the small business owners lack proper knowledge on how to prepare budgets. The findings in this study fill the knowledge gap with regards to the use of budgets by small businesses in the retail and service sectors operating the township of Sharpeville. The findings will make the small business owners aware that budgets are important accounting tools for business and that all business types, including small businesses, can implement budgets as part of their business practice.
M. Tech. (Department of Cost and Management Accounting, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Small, micro and medium enterprises; Budgets; Small businesses; Retail and service sectors; Formal and informal; Township; Sharpeville; Dissertations, Academic -- South Africa.; Cost accounting.; Budget in business.; Accounting.; Small business.